Developing an Integrated VR Infrastructure in Architectural Design Education - Aydin, Serdar; Aktaş, Begüm (Frontiers in Robotics and AI, 2020)
With the advent of computer technology, Virtual Reality (VR) became an integral part of design studios in architecture education. Researchers have been exploring how VR-enhanced design studios can be assessed from a student-centered perspective. This paper illustrates the role of teaching architectural design for developing a novel and contextual curriculum based on an analysis of student feedback. The background focuses on the development of VR-based architectural design education. The methodology frames two digital design ecosystems which are experimented in four undergraduate courses. With an ecosystem-based approach discussed in this paper, a medium-oriented and a content-oriented curriculum are offered for testing students’ reaction to teaching design in VR. In both ecosystems, students are engaged with advanced digital design methods and techniques, which include 3D form-finding, building information modeling, visual programming, coding, and real-time rendering. The study screens the usage of software solutions for the creation of complex virtual environments, covering Blender, Rhinoceros, Unity, Grasshopper and Revit. The implementation of a User Experience Questionnaire (UEQ) comparatively demonstrates the performative qualities of both digital design ecosystems. Results indicate that the intensity of interaction varied in two incomparable, but connate, levels of qualities. The findings suggest that the perspicuity aspects of student interaction bare the risk of “complicated” and “confusing” software. The results further demonstrate a conflict between task-related qualities and non-task related qualities. Additionally, interacting with VR tools in architecture design education is found attractive, stimulating, and original despite low scores on the pragmatic qualities of perspicuity, efficiency, and dependability. The data and results obtained from this study give insight into the planning of design studios in architecture education based on the use of VR and digital methods. Therefore, this study contributes to future research in the contextualization of the design teaching efforts.